2019
DOI: 10.1021/acsomega.9b02270
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration and In-Tissue Polymerization of Photocross-Linked Hydrogel for Effective Fixation of Implants into Cartilage—An In Vitro Study

Abstract: Effective and biocompatible fixation of implants into cartilage defects has yet to be successfully achieved. [Poly-d,l-lactic acid/polyethyleneglycol/poly-d,l-lactic acid] (PDLLA-PEG) is a chondrosupportive scaffold that is photocross-linked using the visible-light photoinitiator lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP). Interestingly, LAP and its monomer DLLA-EG are able to infiltrate the cartilage and form hydrogels upon the detection of light. After the infiltration of LAP and DLLA-EG into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The advantage of this method is we can incorporate another type of biomaterials into pre-made scaffolds at any time. We previously found that five minutes of dipping was adequate for PEGDA penetration in a chip of 5 mm diameter and 2 mm height [ 10 ], and herein we demonstrated the stable form of PEG-infiltrated gels with greater mechanical stiffness constructs. In addition, chondrocyte culture in stiffer matrix material was found to be positively impact to chondrogenesis regarding the nature of articular cartilage as a weight-bearing structure [ 15 ].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The advantage of this method is we can incorporate another type of biomaterials into pre-made scaffolds at any time. We previously found that five minutes of dipping was adequate for PEGDA penetration in a chip of 5 mm diameter and 2 mm height [ 10 ], and herein we demonstrated the stable form of PEG-infiltrated gels with greater mechanical stiffness constructs. In addition, chondrocyte culture in stiffer matrix material was found to be positively impact to chondrogenesis regarding the nature of articular cartilage as a weight-bearing structure [ 15 ].…”
Section: Discussionsupporting
confidence: 62%
“…A technical challenge was how to include PEG polymers into hBMSCs-loaded GH constructs in the middle of chondrogenesis. We adapted a previous method developed in our lab [ 10 ], in which monomers and photoinitiators were first penetrated into native cartilage and then in situ cured within the tissue. A similar strategy was also reported by other research groups [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, glycosaminoglycans (GAGs) have been proven to directly hinder cell adhesion [8]; Second, cell death as a result of surgical preparation at the defect edges reduces integration potential [9]. Third, stress concentration occurs when the biomechanical properties of the implants and native tissues are mismatched under forces, damaging the surrounding tissue and weakening integration [10]. Strategies for enhancing lateral integration include anti-apoptosis agents [9], matrix-degrading enzymes [7], and, more recently, scaffold functionalization to enable direct bonding to adjacent cartilage [11].…”
Section: Introductionmentioning
confidence: 99%
“…Lateral integration is exceedingly difficult to achieve for the following reasons: 1) cartilage displays low metabolism and contains dense, anti-adhesive extracellular matrix (ECM) [ 13 ]. For example, proteins transcribed from the proteoglycan 4 (PRG4) gene, contributors to cartilage's low friction, and glycosaminoglycans (GAGs) have been shown to directly inhibit cell adhesion [ 14 ]; 2) the surgical preparation of defects results in cell death at the defect margins, further reducing integration potential [ 15 ]; and 3) upon loading, mismatches between the biomechanical properties of the implanted scaffolds and native cartilage tissue result in stress concentration, diminishing integration and damaging the surrounding tissue [ 8 , 16 ]. Hence, effective strategies to enhance lateral integration are reported rarely, if ever.…”
Section: Introductionmentioning
confidence: 99%